Imaging and circulating biomarkers: a united approach for secondary tricuspid regurgitation. (14th October 2021) - Spinka, G; Bartko, P E; Heitzinger, G; Teo, E; Prausmueller, S; Arfsten, H; Pavo, N; Winter, M P; Mascherbauer, J; Hengstenberg, C; Huelsmann, M; Goliasch, G
Abstract: Background: Secondary tricuspid regurgitation (STR) is frequent among patients with heart failure with reduced ejection fraction (HFrEF), however inheres considerable diagnostic challenges. The assessment of circulating biomarkers reflecting neurohumoral activation may constitute a valuable supplement to the currently imaging-based diagnostic process. This study therefore sought to investigate (i) the expression of a set of complementary biomarkers in STR, (ii) to evaluate their association with STR severity, and (iii) to analyse whether the combination of neurohormone measurement and echocardiographic grading improves the individual patient risk assessment. Methods: We included 576 HFrEF patients under guideline-directed therapy recording functional, echocardiographic, invasive hemodynamic and biochemical measurements, i.e. N-terminal pro-B-type natriuretic peptide, mid-regional pro-atrial natriuretic peptide (MR-proANP), mid-regional pro-adrenomedullin, C-terminal pro-endothelin-1 (CT-pro-ET1) and copeptin. Results: Plasma levels of aforementioned neurohormones were significantly rising with increasing STR severity (for all P<0.001). Among all measured biomarkers, CT-pro-ET1 and MR-proANP were closest related to severe STR, even after multivariate adjustment for established clinical confounders (adj. OR 1.46; 95% CI 1.11–1.91, P=0.006 and adj. OR 1.45, 95% CI 1.13–1.87, P=0.004, respectively). By means of individual outcome in patients with moderate to severe STR, adding the selected biomarkers (i.e. CT-pro-ET1 and MR-proANP) resulted in a substantial improvement in the discriminatory power regarding long-term mortality (C-statistic: 0.54 vs. 0.65, P<0.001; continuous NRI 57%, P<0.001). Conclusions: Circulating biomarkers closely relate to STR severity and correlate with hemodynamic and morphologic mechanisms of STR. Specifically, MR-proANP and CT-pro-ET1 are closely linked to the presence of severe STR and a combined assessment with the guideline recommended echocardiographic grading leads to a significant improvement of individual risk stratification. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): FWF - Austrian Science Fund